2016
DOI: 10.1016/j.chom.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Transmitted Founder HIV-1 to IFITM-Mediated Restriction

Abstract: SummaryInterferon-induced transmembrane proteins (IFITMs) restrict the entry of diverse enveloped viruses through incompletely understood mechanisms. While IFITMs are reported to inhibit HIV-1, their in vivo relevance is unclear. We show that IFITM sensitivity of HIV-1 strains is determined by the co-receptor usage of the viral envelope glycoproteins as well as IFITM subcellular localization within the target cell. Importantly, we find that transmitted founder HIV-1, which establishes de novo infections, is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
232
5
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(266 citation statements)
references
References 46 publications
27
232
5
2
Order By: Relevance
“…In this context, it is critical to know whether transmitted viruses possess unique biological properties that predispose them to establish new infections more efficiently. This is a controversial topic, because some studies have reported TF-specific traits (22,24,26,52,(55)(56)(57), whereas others have failed to confirm these results (27,28,53,58,59). Some of these discrepancies are likely due to the fact that most previous analyses did not compare HIV-1 strains from transmission pairs.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is critical to know whether transmitted viruses possess unique biological properties that predispose them to establish new infections more efficiently. This is a controversial topic, because some studies have reported TF-specific traits (22,24,26,52,(55)(56)(57), whereas others have failed to confirm these results (27,28,53,58,59). Some of these discrepancies are likely due to the fact that most previous analyses did not compare HIV-1 strains from transmission pairs.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that resisting IFNα‐induced antiviral effects provides a selection advantage during HIV‐1 transmission and the acute phase of infection. It was also shown that TF HIV‐1 strains are particularly resistant to inhibition by IFN‐induced transmembrane proteins (IFITMs), which impair viral entry into target cells . Furthermore, pandemic group M (major) HIV‐1 strains counteract the IFN‐inducible restriction factor tetherin more efficiently than rare group N and P HIV‐1 isolates, which resulted from independent zoonotic transmissions .…”
Section: Interferonsmentioning
confidence: 99%
“…In particular, transmitter/founder viruses have been found to be more resistant to IFITM restriction than viruses isolated from later times during infection; the later viruses may gain sensitivity as a result of escape from concomitant neutralizing antibody responses [17], although this in turn raises the question as to the relative relevance of IFITM as an in vivo restriction mechanism compared to antibody-driven selection.…”
Section: Introductionmentioning
confidence: 99%